Tourism and Regenerationin World Heritage Urban Areas: A Systematic Literature Review and Bibliometric Analysis - Aslani, Ehsan; Kaczmarek, Jacek (Geographica Pannonica, 2025)
Tourism and regeneration are two interrelated factors that have a significant impact on World Heritage urban areas (WHUAs), places of outstanding cultural and historical values. However, the literature on the relationship between tourism and regeneration and their impact on these areas is still scarce and fragmented. This paper aims to provide a comprehensive and systematic review of the existing studies on tourism and regeneration in WHUAs and to identify the main research gaps and directions for future research. In this regard, we reviewed English published articles, conference proceedings, and book chapters indexed on Web of Science (WoS) and Scopus databases until 2023. We analyzed the publication trends, the most influential journals and publishers, the main research topics and methods, and the most applied approaches. The results revealed that in recent years, the Historic Urban Landscape, and culture-led urban regeneration approaches, as well as concepts such as authenticity and sustainability, have received the attention of researchers in this field. However, the literature also shows some limitations, such as a lack of theoretical and review studies, quantitative approaches, and a shortage of multiple-case studies. In addition, the factors for failure, consequences, and procedural solutions extracted as the key themes of the related projects. Based on these findings, this review provides insights valuable to researchers, urban planners, and policymakers involved in the conservation and development of these culturally valuable areas in ways that balance tourism growth with heritage preservation.